Protection granted to the worker based on personal consideration in the Saudi labor system - Ahmed Abdullah Al-Qarni (International Journal of Law Research and Studies, 2025)
This research aims to demonstrate the protection provided to workers based on personal considerations in the Saudi labor system. This is achieved through an analytical study of the relevant legal texts and an induction of their contents, which embody the principle of protecting the weaker party in the contractual relationship. The importance of this study lies in its addressing a delicate aspect of labor protection: the worker’s personal considerations, which Saudi regulators take into account when regulating the employment relationship. The research revealed that the forms of personal protection for workers are embodied in three considerations. The first is gender, which has been specifically provided to working women based on their nature, such as maternity and waiting period leave, breastfeeding periods, pregnancy care, and the requirement of a nursery. The second consideration is protection based on nationality, as the system gives priority to Saudi citizens in obtaining job opportunities and obliges employers to train and qualify citizens to replace expatriate workers. Then there is age-based protection, which aims to protect the rights of minors and prevent them from being employed in strenuous or dangerous work. The study concludes that the Saudi labor system has provided personal protection for the worker, thereby achieving humane protection for the worker that is consistent with the provisions of Islamic law and international labor principles.